1982
DOI: 10.1021/j100213a025
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the visible spectra of nitroxides and relation to nitrogen hyperfine splitting constants. Nonempirical polarity scales for aprotic and hydroxylic solvents

Abstract: The absorption spectra of nitroxides in the visible region are highly solvatochromic. In this paper we report some data on solvent effects on the band energy, ET, of 2,2,6,6-tetramethylpiperidinyl-1 -oxy (TEMPO) and 4-oxo-2,2,6,6-tetramethylpiperidinyl-l-oxy (OTEMPO). Special attention has been given to hydroxylic solvents and particularly to a series of reference solvents of graded hydrophilicity, dodecane, primary alcohols, ethanol-water and methanol-water mixtures, and water. The polarity index H, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 0 publications
6
89
0
Order By: Relevance
“…(7)) will depend on the concentration of proton-donor -OH groups in the different solvents. The latter is determined from the densities and molecular weights, together with additional data for ethanol-water mixtures from Mukerjee et al [42]. DOXYL, respectively, in an aprotic solvent of polarity f ðe r Þ=ð1 À 1 4 f ðe r ÞÞ % 0:5 that are predicted from the data in Table 1.…”
Section: Dependence Of a N O On Hydrogen Bondingmentioning
confidence: 99%
“…(7)) will depend on the concentration of proton-donor -OH groups in the different solvents. The latter is determined from the densities and molecular weights, together with additional data for ethanol-water mixtures from Mukerjee et al [42]. DOXYL, respectively, in an aprotic solvent of polarity f ðe r Þ=ð1 À 1 4 f ðe r ÞÞ % 0:5 that are predicted from the data in Table 1.…”
Section: Dependence Of a N O On Hydrogen Bondingmentioning
confidence: 99%
“…The magnitude of this effect can be estimated employing the nonempirical polarity index, H, introduced by Mukerjee et al 15 which is defined to be the ratio of molar concentration of OH dipoles in a solvent or solvent mixture to that in water. Assuming ideal mixing as a first order approximation, it is easily shown that the change in H in going from zero to 52 mM 16DSE is approximately 8 × 10 -3 .…”
Section: Methodsmentioning
confidence: 99%
“…Solutions of TEMPOstearate were prepared in a series of mixtures of ethanol-water and ethanol-1,4-dioxane. The hydration index H of each solution mixture [35] defined as the ratio of the molar concentration of OH dipoles in the solution mixture to that of pure water is calculated according to Eq. (5) from Ref.…”
Section: Resultsmentioning
confidence: 99%